AKTIVITAS ANTIOKSIDAN DAN TINGKAT KESUKAAN SUSU JAGUNG MANIS (Zea mays saccharata) DENGAN PENAMBAHAN EKSTRAK JAHE (Zingiber officinale roscoe) - Uri, Nur Natalia; Mamuaja, Christine F.; Koapaha, Teltje (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
Processing sweet corn milk is one way to diversify sweet corn products as a substitute for animal milk so that it is suitable for those who are on a diet and for people who are intolerant of lactose. Pure milk in the processing of sarabba can also be replaced with sweet corn milk with the addition of ginger extract. This study aims to determine the right concentration of ginger extract on antioxidant activity and measure the level of preference of panelists on sweet corn milk with the addition of ginger extract. This study used a completely randomized design with 4 treatments (addition of ginger extract as much as 2%, 3%, 4%, 5% and control treatment). The parameters tested were antioxidant activity and organoleptic testing (taste, aroma and color) of sweet corn milk with the addition of ginger extract. The results of the study showed that sweet corn milk samples with the addition of ginger extract had moderate to strong antioxidant activity. In accordance with the parameters of the IC50 value, the lowest value was 77.33 Î¼g / ml on the addition of 5% ginger extract which had strong antioxidant properties and the highest IC50 value of 110.81 Î¼g / ml in 2% addition of ginger extract had antioxidant properties is being In the organoleptic test, panelists preferred taste and color in the treatment of sweet corn milk without the addition of ginger extract, while the aroma of sweet corn milk with the addition of ginger extract was the most preferred in the treatment of the addition of as much as 2%. Keywords: Sweet corn milk, Ginger, Antioxidant Activity